The lake - Preston, Natasha (New York : Delacorte Press, 2021)
Seventeen-year-old best friends Esme and Kayla return to Camp Pine Lake as counselors in training, but the dark secret they have been hiding for nine years is back to haunt them.
Includes excerpt of The twin.
Ages 12 and up.
HL550L
Decoding demand: 93 (very high) Semantic demand: 100 (very high) Syntactic demand: 81 (very high) Structure demand: 88 (very high)
Keywords: Camps -- Juvenile fiction; Secrecy -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Camp counselors -- Juvenile fiction; Young adult fiction; Detective and mystery fiction